The effects of geographical origin and virus infection on the saffron (Crocus sativus L.) quality. (15th October 2019) - Parizad, Shirin; Dizadji, Akbar; Habibi, Mina Koohi; Winter, Stephan; Kalantari, Siamak; Movi, Shahrbanoo; Lorenzo Tendero, Candida; Alonso, Gonzalo L.; Moratalla-Lopez, Natalia
Highlights: Saffron's major secondary metabolites vary by various geographical origin. Saffron latent virus (SaLV) infection modifies the secondary metabolites content. HPLC is more adequate than UV–vis spectrophotometry to determine these metabolites. Effects of geographical origin is notably greater than SaLV on saffron metabolites. Abstract: Saffron is appreciated by its colour, taste, and aroma. To examine the effect of abiotic and biotic stress on these main properties, in the span of 2014–2016, saffron stigmas were collected from major different saffron cultivation areas of Iran and saffron quality was estimated. The quality of saffron was assessed by ultraviolet-visible spectroscopy following the ISO3632:2011 standard. However, the composition and concentration of crocetin esters, picrocrocin, safranal, and kaempferols, the most critical compounds determining the properties and quality of saffron can vary with the geographical origin and virus effects, being more accurate High-Performance Liquid Chromatography and Diode Array Detection (HPLC-DAD) methods were used to analyze saffron quality. Using HPLC-DAD we analyzed saffron plants grown at various conditions (considering altitude, temperature, and precipitation/rainfall) and in presence/absence of virus infections; we found that edaphoclimatic and cultivation conditions significantly determine the quality of the spice and the presence of virus modifies the content of its metabolites.